2021
DOI: 10.2147/cmar.s285118
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA hsa_circ_0005909 Promotes Cell Proliferation of Osteosarcoma Cells by Targeting miR-338-3p/HMGA1 Axis

Abstract: Objective Osteosarcoma (OS) is the most common malignant bone tumor in the pediatric population. The main goal of this study is to investigate the role of hsa_circ_0005909 and the underlying signaling pathway involved in OS. Methods Cell proliferation was measured using a CCK-8 assay kit and clone formation assay. Change of RNA and protein expression was determined using RNA extract and quantitative real time PCR (RT-qPCR) assay and Western blotting, respectively. CircI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…PI3K/Akt and ERK pathways are crucial oncogenic pathways in the progression of OS. Zhang et al 29 reported that CircRNA hsa_circ_0005909 promotes the development of OS by enhancing the activation of the PI3K/Akt and ERK pathways. Wang et al 30 demonstrated that hyperactivation of epidermal growth factor receptor (EGFR) promotes cell proliferation and metastasis by activating PI3K/Akt and ERK pathways in OS.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt and ERK pathways are crucial oncogenic pathways in the progression of OS. Zhang et al 29 reported that CircRNA hsa_circ_0005909 promotes the development of OS by enhancing the activation of the PI3K/Akt and ERK pathways. Wang et al 30 demonstrated that hyperactivation of epidermal growth factor receptor (EGFR) promotes cell proliferation and metastasis by activating PI3K/Akt and ERK pathways in OS.…”
Section: Discussionmentioning
confidence: 99%
“…miR-338-3p has been widely reported to be involved in human cancer development and progression. In osteosarcoma, the circRNA hsa_circ_0005909/miR-338-3p/HMGA1 axis promotes tumor cells proliferation [ 14 ]; the CASC15/miR-338-3p/RAB14 axis induces tumor cells growth, migration, and invasion in vitro and in vivo [ 15 ]. In thyroid cancer, the circHIPK3/miR-338-3p/RAB23 axis is shown to activate tumor cells tumorigenesis and invasiveness in vitro [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, we observed that silence of circ_0005909 suppressed the proliferative and metastatic abilities of NSCLC cells as well as drug resistance, indicating circ_0005909 might be a therapeutic target of NSCLC. Previously, the tumor-promotive roles of circ_0005909 in osteosarcoma were also reported [ 22 ]. Thus, whether there was a cross-talk for the efficiency and specificity of circ_0005909 needed to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA RHOT1 promoted metastasis and suppressed ferroptosis via the miR-106a-5p/STAT3 axis in breast cancer [ 26 ]. Previously, circ_0005909 was shown to sponge miRNA-338-3p and miR-936 in osteosarcoma, thus promoting the progression of osteosarcoma [ 13 , 22 ]. These findings suggested that circ_0005909 is a potential therapeutic target for osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%